The Evolution Civil-Military Relations and Democratization in the Balkans - Celik, Nihat (Journal of Regional Security, 2018)
Following the dissolution of the Soviet Union and Yugoslavia, in addition to the political and economic orders, the structure of civil-military relations also began to change. The paper will provide an insight into the patterns of civil-military relations from a historical perspective. The main argument of the paper is that even though serious and mostly successful first generation reforms are made in the field of democratic civil-military relations, there are still some problems regarding the second generation reforms. In order to address these problems, the evolution of civil-military relations in the post-Communist era will be analyzed with a focus on successes and failures. After sorting out current problems, it will secondly try to answer the question what should be done in order to establish a more democratic structure of civil-military relations.